Efficient synthesis of varenicline - Pasikanti, Srinivas; Reddy, D. Srinivasa; Venkatesham, B.; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2010)
Synthesis of varenicline the antismoking drug has been achieved in six steps with 10% overall yield. A Diels-Alder reaction, oxidative cleavage of an olefin and reductive amination remain as key steps in the synthesis (C) 2009 Elsevier Ltd. All rights reserved.

Enantiospecific synthesis of sex pheromone of the obscure mealybug from pantolactone via tandem conjugate addition/cyclization - Hajare, Atul K.; Datrange, Laxmikant S.; Vyas, Samir; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2010)
An efficient synthesis of an enantiomer of insect's natural pheromone is reported starting from chiral pool D-(-)-pantolactone. Highly stereoselective tandem conjugate addition/cyclization sequence and hydrogenation of exocyclic double bond are the key steps in the present synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction

Enantiodivergent routes to (+) and (-)-novioses from (-)-pantolactone - Rajesh, B. M.; Shinde, Madhuri V.; Kannan, M.; Srinivas, Gujjary; Iqbal, Javed; Reddy, D. Srinivasa (RSC Advances, 2013)
Noviose, a rare sugar moiety present in many biologically interesting molecules such as novobiocin and tiacumicin was obtained through formal synthesis in (+)- and (-)-forms starting from commercially available (-)-pantolactone in an enantiodivergent manner.

Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide

Enantiospecific synthesis of both enantiomers of the longtailed mealybug pheromone and their evaluation in a new zealand vineyard - Ramesh, Remya; Bell, Vaughn; Twidle, Andrew M.; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2015)
The irregular monoterpenoid sex pheromone of Pseudococcus longispinus and its enantiomer were prepared from the corresponding bornyl acetates. The use of readily accessible chiral starting materials and lactone lactone rearrangement are the highlights of the present synthesis. The biological activities of the two enantiomers and racemic mixture were tested in a New Zealand vineyard. The (S)-(+)-enantiomer was significantly more attractive to P. longispinus males than the racemic mixture or the (R)-(-)-enantiomer.

Enantiospecific formal synthesis of inthomycin C - Athawale, Paresh R.; Kashinath, K.; Reddy, D. Srinivasa (Chemistry Select, 2016)
An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)-inthomycin C and (3S)-inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural product inthomycin C.

Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy - Shivapurkar, Rupali; Hingamire, Tejashri; Kulkarni, Akshay S.; Rajamohanan, P. R.; Reddy, D. Srinivasa; Shanmugam, Dhanasekaran (Scientific Reports, 2018)
Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume similar to 20 times more glucose, and trophozoites metabolize similar to 6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage parasites, exclusively. We demonstrate this using potent and mechanistically distinct antimalarial compounds such as chloroquine, atovaquone, cladosporin, DDD107498 and artemisinin. Our findings indicate that ring stage parasites are inherently more tolerant to antimalarial inhibitors, a feature which may facilitate emergence of drug resistance. Thus, there is a need to discover novel antimalarial compounds, which are potent and fast acting against ring stage parasites. The NMR method reported here can facilitate the identification of such molecules.

Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.